The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7150/ijms.28382
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic Implications of Cytokines Secretion during Liver Transplantation Surgery

Abstract: We introduce the following issues of the cytokines secretion during liver transplantation surgery in this review article; 1) the aspect of cytokines secretion during liver transplantation surgery, 2) the evidences of association of cytokines concentration with post-transplantation graft survival, 3) a variety of factors that may influence the secretion of cytokines during liver transplantation, 4) pro-inflammatory and anti-inflammatory cytokine balance during the surgery, and 5) the issues of T helper 1 and T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Indeed, depleting ESRP2 exacerbated alcohol-induced steatohepatitis in mouse models. As inflammatory cytokines are involved in liver injury in many disease settings (90)(91)(92), ESRP2 suppression and adult-to-fetal reprogramming were also observed in a carbon tetrachloride (CCl 4 )-induced liver fibrosis model (71). Downregulation of ESRP2 activates a neonatal splicing program and causes exon skipping in the Yap1 and Tead1 genes, rewiring Hippo signaling and supporting progenitor cell proliferation upon liver injury (55).…”
Section: Esrp2mentioning
confidence: 99%
“…Indeed, depleting ESRP2 exacerbated alcohol-induced steatohepatitis in mouse models. As inflammatory cytokines are involved in liver injury in many disease settings (90)(91)(92), ESRP2 suppression and adult-to-fetal reprogramming were also observed in a carbon tetrachloride (CCl 4 )-induced liver fibrosis model (71). Downregulation of ESRP2 activates a neonatal splicing program and causes exon skipping in the Yap1 and Tead1 genes, rewiring Hippo signaling and supporting progenitor cell proliferation upon liver injury (55).…”
Section: Esrp2mentioning
confidence: 99%
“…During this process, the liver will produce and release a large number of cytokines, including chemokines and proinflammatory cytokines. Cytokines, which can exert a wide range of effects upon proinflammatory and regulatory properties, might be considered potential therapeutic targets for selective suppression or enhancement of the immune responses in recipients [24]. In the mouse OLT model, we found that serum ALT and AST showed a temporally depen-dent increase after liver transplantation, indicating that hepatocytes were damaged.…”
Section: Discussionmentioning
confidence: 83%
“…Surgery, including organ transplantation, causes an increase in inflammation and oxidative stress and an increase in cytokines, cortisol and other counter-regulatory hormones. [10][11][12][13] This results in insulin resistance and hyperglycemia, and the degree to which these consequences occur is related to the intensity of the surgical injury. 10 The The development of hyperglycemia has been associated with increased rates of complications, infection, and mortality 14,15 and the hyperglycemia itself has been associated with increased inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%